ANALISIS PERBANDINGAN LAPORAN KEUANGAN PADA PT. RIMBA KARA RAYATAMA - Istimaroh Istimaroh (Jurnal Ekonomi dan Manajemen, 2017)
The purpose of the research is want to know the positioning for the company Specially in PT.Rimaba Karya Rayatama. Because with the e statement needed to get information more detail about the operational of the company already gotten in each year and the financial positioning of the company some basic tools can be used are : the first is Trend analysis that the technic for evaluation the financial statement in the period of the company to calculate the up and down of financial for each transaction, for financial of company with compare between this year and last year. The second is common size analysis that the ethnic for evaluating financial report to account for each item in the financial statement and in percentage to basic value in the past is Total of Assets for balance sheet and total net sales for income statement. The third is Financial ratio analysis thy are liquidity ratio, solvability ratio and profitability ratio.